Low risk of new dysplastic lesions in an inflammatory bowel disease population study with dye chromoendoscopy - Sicilia, Beatriz; González-Lama, Yago; Velayos, Benito; Suárez, Patricia; Maroto-Martín, Carlos; Nuñez, Aljandro; Hernández, Luis; Sáiz-Chumillas, Rosa M.; Relea, Lucia; Fernández-Salazar, Luis; Sierra-Ausín, Mónica; Barrio Andrés, Jesús; Muñoz, Fernando; Arias García, Lara (Endoscopy International Open, 2023)
Background and study aims Rates of new dysplastic lesions or cancer progression after first dye chromoendoscopy in the era of high-definition endoscopy have yet to be determined.Patients and methods A multicenter, population-based, retrospective cohort study was performed in seven hospitals in Spain. Patients with inflammatory bowel disease and fully resected (R0) dysplastic colon lesions under surveillance with high-definition dye-based chromoendoscopy were sequentially enrolled between February 2011 and June 2017, with a minimum endoscopic follow-up of 36 months. The aim was to assess the incidence of developing more advanced metachronous neoplasia by analyzing possible associated risk factors.Results The study sample included 99 patients and 148 index lesions (145 low-grade dysplasia lesions and three high-grade dysplasia [HGD] lesions with a mean follow-up of 48.76 months [IQR: 36.34–67.15]). The overall incidence of new dysplastic lesions was 0.23 per 100 patient-years, 1.15 per 100 patients at 5 years and 2.29 per 100 patients at 10 years. A history of dysplasia was associated with a higher risk of developing any grade of dysplasia during follow-up (P = 0.025), whereas left colon lesions were associated with a lower risk (P = 0.043). The incidence of more advanced lesions at 1 year and 10 years was 1 % and 14 % respectively, with lesion size > 1 cm being a risk factor (P = 0.041). One of the eight patients (13 %) with HGD lesions developed colorectal cancer during follow-up.Conclusions The risk of dysplasia progressing to advanced neoplasia and, specifically, the risk of new neoplastic lesions after endoscopic resection of colitis-associated dysplasia, are both very low.